Development of a 100 mW-Class 94 GHz High-Efficiency Single-Series Rectifier Feed by Finline for Micro-UAV Application. (21st August 2020) - Matsui, Kosumo; Komurasaki, Kimiya; Hatakeyama, Waku; Shimamura, Kohei; Fujiwara, Kohei; Yamaoka, Hidehiko
Abstract : Wireless power transfer (WPT) is one solution to realize long flight times and accommodate various missions of micro-uncrewed aerial vehicles (MAVs). Reducing the constraint of power transmission distance and realizing high beam efficiency are possible because of the high directivity of WPT using millimeter wave (MMW) methods. Nevertheless, no report of the relevant literature describes an investigation of sending power to an MAV using MMW because MMW rectennas have low efficiency. The purpose of our study is to conduct fundamental research of a high-efficiency and high-power rectenna at 94 GHz aimed at MAV application using MMW. As described herein, we developed and evaluated a 100-mW-class single-diode rectifier at 94 GHz with a finline of a waveguide (WG) to a microstrip-line (MSL) transducer. With the optimum load of 150 Ω at input power of 128 mW, the output DC power and rectifying efficiency were obtained respectively as 41.7 mW and 32.5%. By comparison to an earlier study, measurement of 94 GHz rectifiers under high power input becomes more accurate through this study.